2018
DOI: 10.1177/0004867418804066
|View full text |Cite
|
Sign up to set email alerts
|

Australia’s ‘Better Access’ scheme: Has it had an impact on population mental health?

Abstract: Background: Australia introduced the Better Access scheme in late 2006, which resulted in a large increase in the provision of mental health services by general practitioners (GPs), clinical psychologists, other psychologists and allied health professionals. It is unknown whether this increase in services has had an effect on the mental health of the population. Methods: The following data were examined: per capita use of mental health services provided by GPs, clinical psychologists, other psychologists, alli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
90
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(98 citation statements)
references
References 23 publications
6
90
2
Order By: Relevance
“…In the present study, it was noted that the Medicare top‐tier allows clinical psychologists to provide “psychological therapy,” while the second‐tier only allows counselling psychologists to offer “focussed psychological strategies.” This split was viewed as an insult, given that the core competencies and definition of a counselling psychologist include “tailored psychotherapies” for “complex and severe mental health disorders” (APAC, , p. 20). Evidently, the far‐reaching implications of the two‐tier system for consumers' freedom of choice and treatment outcomes, as well as the diversity of the psychology profession, are of considerable concern, particularly given the lack of an evidence base or rationale for the two‐tier system as highlighted by respondents in this study and previously noted elsewhere (Jorm, , ; King, ; Meteyard & O'Hara, ; Pirkis, Harris, Hall, & Ftanou, ).…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…In the present study, it was noted that the Medicare top‐tier allows clinical psychologists to provide “psychological therapy,” while the second‐tier only allows counselling psychologists to offer “focussed psychological strategies.” This split was viewed as an insult, given that the core competencies and definition of a counselling psychologist include “tailored psychotherapies” for “complex and severe mental health disorders” (APAC, , p. 20). Evidently, the far‐reaching implications of the two‐tier system for consumers' freedom of choice and treatment outcomes, as well as the diversity of the psychology profession, are of considerable concern, particularly given the lack of an evidence base or rationale for the two‐tier system as highlighted by respondents in this study and previously noted elsewhere (Jorm, , ; King, ; Meteyard & O'Hara, ; Pirkis, Harris, Hall, & Ftanou, ).…”
Section: Discussionmentioning
confidence: 71%
“…It has narrowed clients' freedom of choice, such that a therapy pathway may be chosen based on least financial disadvantage, rather than appropriateness of fit. The structure of the two‐tier model suggests to the consumer that clinical psychologists are somehow better trained or equipped to deal with complex mental health disorders when there is, in fact, no evidence that a clinical psychologist achieves any better client outcomes when compared to any other psychologist (Grant, Mullings, & Denham, ; Pirkis, Harris, Hall, & Ftanou, ; Jorm, ; Jorm, ). Consequently, respondents reported that the model itself is harming both the consumer and the profession, through funnelling an uninformed public into higher rebated clinical psychology services when a counselling psychologist is equally trained to treat the presenting issue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations